The efficiency of inverted index and cluster searches - Voorhees, Ellen (1986)
The processing time and disk space requirements of an inverted index and top-down cluster search are compared. The cluster search is shown to use both more time and more disk space, mostly due to the large number of cluster centroids needed by the search. When shorter centroids are used, the efficiency of the cluster search improves, but the inverted index search remains more efficient.
Keywords: Information storage and retrieval systems; Search theory; Theory